Self Help Group- A Panaca for Financial Inclusiveness - Saxena, Kavita (Journal of Commerce and Trade, 2013)
Rapid and sustained poverty requires inclusive growth that allows people to contribute to and benefit from economis growth. Rapid pace of growht is unquestionably necessary for substanitial poverty reduction, but for this growth to be sustainable in the long run, it should be broad-based across sectors, and inclusive of the large part of the country’s labour force, In this content it is interesting to note to school of thoughts- OECD Development Assistance Committee’s pro-Poor approach’ which is mainly interested in the welfare of the poor. India has an extensive network of banking systems and it will need to find ways to bring improvements within the existing financial credit delivery mechanisms and evolve new models for extending their outreach instead of promoting parallel systyms of financial delivery. Financial literacy is the key for financial inclusion but it is weak particularly among rural population. There is a need to simultaneously focus on the financial literacy besides the delivery and access.Significant investment from various players such as banks, governments, NGOs and academia has to be made. SHGs have proved to be a sound platform to educate their members on financial parameters.